The function and clinical implication of circular RNAs in lung cancer - Jiang, Xiulin; Duan, Lincan (Frontiers in Oncology, 2022)
Lung cancer is the leading cause of cancer-related deaths worldwide. Despite the recent advent of promising new targeted therapies, lung cancer diagnostic strategies still have difficulty in identifying the disease at an early stage. Therefore, the characterizations of more sensible and specific cancer biomarkers have become an important goal for clinicians. Circular RNAs are covalently close, endogenous RNAs without 5′ end caps or 3′poly (A) tails and have been characterized by high stability, abundance, and conservation as well as display cell/tissue/developmental stage-specific expressions. Numerous studies have confirmed that circRNAs act as microRNA (miRNA) sponges, RNA-binding protein, and transcriptional regulators; some circRNAs even act as translation templates that participate in multiple pathophysiological processes. Growing evidence have confirmed that circRNAs are involved in the pathogenesis of lung cancers through the regulation of proliferation and invasion, cell cycle, autophagy, apoptosis, stemness, tumor microenvironment, and chemotherapy resistance. Moreover, circRNAs have emerged as potential biomarkers for lung cancer diagnosis and prognosis and targets for developing new treatments. In this review, we will summarize recent progresses in identifying the biogenesis, biological functions, potential mechanisms, and clinical applications of these molecules for lung cancer diagnosis, prognosis, and targeted therapy.